PENERAPAN PEMBELAJARAN BERBASIS PERMAINAN (GAME-BASED LEARNING) PADA TEORI KONSTRUKSI BANGUNAN - Prasetyo Ady Nugroho Putra (CV. ADIBA AISHA AMIRA, 2024)
Abstract The growth of digital technology has opened up new opportunities in learning methods, including the application of Game-Based Learning (GBL) in the field of building construction engineering education. This research aims to explore the impact and benefits of implementing GBL in teaching building construction theory through a comprehensive literature review. The literature review method was used to analyze empirical studies related to the use of games in learning building construction concepts, such as building design, project management, cost calculation, and construction simulation. The review results show that GBL can increase student motivation and engagement, facilitate visualization and understanding of complex concepts, and provide an immersive and interactive learning experience. However, the successful implementation of GBL depends on factors such as the design of games that match the learning objectives, integration with the curriculum, teacher training, and the availability of adequate technological infrastructure. This study concludes that GBL has significant potential in improving the quality of teaching building construction theory and preparing students for challenges in the dynamic world of work. Recommendations for further research and practical implementation are also presented to optimize the benefits of GBL in building construction engineering education.